ANALYSIS THE BRAND SWITCHING OF CONSUMER OF WARDAH COSMETICS IN MANADO - Herlambang, Agnes; Lapian, Joyce S.L.H.V.; Pandowo, Merinda H. C. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: The use of cosmetics in Indonesia is considered to be growing rapidly, this is evident from the increasing consumption of cosmetics every year and this is reinforced by changes in people's lifestyles today. The purpose of this study was to determine the shifting of consumer brands in Manado and how to see opportunities to find out how brand displacement was caused by halal labels on Wardah brands. This study uses an exploratory approach with in-depth interviews to collect data from fifteen informants. The qualitative approach used in this study illustrates the importance of brand transfer for Muslim female students. The results showed that they felt the halal importance of the halal labeled brand and included halal products to use the Wardah brand especially for Muslim female students to fulfill Islamic law, be safe and suitable from the brand, as well as low prices to make purchasing decisions and switch brands from one brand to brand Wardah. Based on the findings, the recommendations of this study are for cosmetics consumers Wardah in Manado, especially Muslim female students to maintain these 3 indicators to become loyal customers of trusted brands in accordance with the needs and Islamic law. Keywords: brand switching, halal product, consumer switching, variety seeking, promotion.